Minding the knowledge-action gap: Results from a mixed-methods study of antimicrobial use among dairy farmers in central Uganda - Anica Buckel; Clovice Kankya; Mark A. Caudell; Tabitha Kimani; Alice Namatovu; Lordrick Alinaitwe; James Natweta Baguma; Rogers Musiitwa; Methodius Tubihemukama; Junxia Song; Emmanuel Kabali; Jorge Pinto Ferreira; et al. (PLoS ONE, 2026)
Antimicrobial resistance (AMR) presents a growing threat to global health and food security, accelerated by human behaviours such as suboptimal use patterns. While the negative consequences of AMR will be particularly severe in low- and middle-income countries, relatively little is known about the extent and frequency of behaviours that contribute to AMR in these regions. This mixed-methods study, which included a cross-sectional survey, examines knowledge, attitudes, and practices related to antimicrobial use (AMU) among 417 smallholder dairy farmers in Uganda’s Wakiso, Kampala, and Mukono districts. We found that (1) farmers’ AMU practices were associated with attitudes toward veterinarians and access barriers, with many relying on private veterinarians due to challenges accessing public animal health services; and; and (2) findings support the concept of a ‘knowledge-action gap,’ as AMR knowledge and belief items were weakly associated with prudent antimicrobial use and related practices in our exploratory models, These findings highlight the need to rethink the current reliance on conventional knowledge-attitude-practice (KAP) interventions alone. Instead, behaviour-centred approaches informed by theory-driven behaviour change frameworks, along with interdisciplinary collaboration, may offer more profound insight into the multifaceted factors that shape AMR-associated practices and inform more tailored interventions. Finally, given the prominent role of private veterinary service providers as trusted points of contact for farmers, there is a clear need to foster partnerships that formally recognise and engage these actors in stewardship efforts while ensuring alignment with national policy and regulatory oversight.